A thiol-activated fluorogenic probe for detection of a target protein. Issue 43 (9th May 2022) - Li, Hui; Lee, Chang-Hee; Shin, Injae
Abstract : A novel fluorogenic probe for facile and efficient detection of a target protein that binds to a bioactive small molecule was developed. Abstract : A novel fluorogenic probe for facile and efficient detection of a target protein that binds to a bioactive small molecule was developed. The probe was composed of a thiol-activated fluorogenic moiety bearing an alkyne tag and a protein binding ligand linked to a photoreactive protein labeling group. The new probe in conjunction with affinity chromatography and mass spectrometry was utilized to identify a target protein in cell lysates.